2014
DOI: 10.1128/jvi.03609-13
|View full text |Cite
|
Sign up to set email alerts
|

A Temporospatial Map That Defines Specific Steps at Which Critical Surfaces in the Gag MA and CA Domains Act during Immature HIV-1 Capsid Assembly in Cells

Abstract: During HIV-1 assembly, Gag polypeptides target to the plasma membrane, where they multimerize to form immature capsids that undergo budding and maturation. Previous mutational analyses identified residues within the Gag matrix (MA) and capsid (CA) domains that are required for immature capsid assembly, and structural studies showed that these residues are clustered on four exposed surfaces in Gag. Exactly when and where the three critical surfaces in CA function during assembly are not known. Here, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
147
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(181 citation statements)
references
References 65 publications
32
147
2
Order By: Relevance
“…Shortly after translation, Gag co-opts a cytoplasmic host complex that contains RNA granule proteins (also called processing body or P body proteins), (Reed et al, 2012). Two of the proteins in this complex are host enzymes that facilitate assembly - ABCE1 and DDX6 (Reed et al, 2012; Robinson et al, 2014; Zimmerman et al, 2002). A third co-opted host protein, Staufen, is an RNA binding protein that facilitates Gag multimerization and RNA packaging [reviewed in (Cochrane et al, 2006)].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly after translation, Gag co-opts a cytoplasmic host complex that contains RNA granule proteins (also called processing body or P body proteins), (Reed et al, 2012). Two of the proteins in this complex are host enzymes that facilitate assembly - ABCE1 and DDX6 (Reed et al, 2012; Robinson et al, 2014; Zimmerman et al, 2002). A third co-opted host protein, Staufen, is an RNA binding protein that facilitates Gag multimerization and RNA packaging [reviewed in (Cochrane et al, 2006)].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that Gag progresses through a sequential pathway of assembly intermediates, which are described by their sedimentation values (∼10S, ∼80S, ∼150S, and ∼500S). The high-molecular-mass assembly intermediates (the ∼80S, ∼150S, and ∼500S complexes) contain gRNA and other viral proteins, as well as cellular proteins, such as ABCE1 and DDX6, that dissociate when assembly is completed (Dooher et al, 2007; Reed et al, 2012; Robinson et al, 2014; Zimmerman et al, 2002). Consistent with this model, assembly-defective Gag mutants are arrested at specific steps in this assembly pathway, resulting in accumulation of the assembly intermediates that precede the point of blockade (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DDX6 binds extensively onto mRNAs and has been reported to chaperone gRNA-Gag associations (Ernoult-Lange et al, 2012; Reed et al, 2012; Robinson et al, 2014; Yu et al, 2011). Moreover, EDC4 functions as a binding platform that recruits important PB proteins including the decapping enzymes Dcp1 and 2, thereby enhancing their activities (Chang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…ABCE1 codes for ribonuclease L inhibitor, which regulates various biological functions, such as ribosome biosynthesis and recycling, as well as HIV capsid assembly [23, 24]. …”
Section: Discussionmentioning
confidence: 99%